Platelet-Activating Factor Promotes Neutrophil Activation and Platelet–Neutrophil Complex Formation - Wohlgemuth, Lisa; Knapp, Christiane Leonie; Vidoni, Laura; Hug, Stefan; Müller, Paul; Mohamed, Adam Omar Khalaf; Dietz, Annika; Stratmann, Alexander Elias Paul; Stukan, Laura; Höpfer, Larissa Melina; Thomaß, Bertram Dietrich; Koller, Alexander Sebastian; et al. (Scandinavian Journal of Immunology, 2025)
Controlling excessive inflammation remains an unmet clinical need, for example, during sepsis or after severe injuries. Platelet-activating factor (PAF) is central in thromboinflammatory processes. However, its role in the interaction of platelets and neutrophils requires further insights. Therefore, we elucidated PAF-related neutrophil activation, including platelet–neutrophil complex (PNC) formation and investigated potential strategies to modulate PAF-related inflammation. For the translation of the PAF-mediated inflammation, we applied an animal-free human ex vivo whole blood model. The neutrophil phenotype, its function, and PNC formation were studied by flow cytometry and platelet-related activity was assessed by light microscopy and aggregometry. PAF induced a rapid and dose-dependent change in neutrophil phenotype, as evidenced by CD10, CD11b, and CD66b upregulation and CD62L downregulation. Moreover, PAF increased the generation of reactive oxygen species (ROS), phagocytic activity and PNC formation. Interestingly, PNCs displayed significantly enhanced ROS formation and phagocytosis compared to neutrophils without attached platelets, whereas these differences were not observed regarding phenotype changes. Furthermore, the findings were confirmed in a clinically relevant ex vivo whole blood model of lipopolysaccharide- or PAF-driven inflammation. In summary, the present study elucidates PAF-driven effects on neutrophils and their interaction with platelets. The findings might help in developing therapeutic approaches to modulate PAF-related thromboinflammation, for example, during sepsis.
CRIS-Team Scopus Importer:2025-08-08
Keywords: animal-free ex vivo whole blood model; neutrophils; platelet-activating factor; platelet–neutrophil complexes; thrombocytes; thromboinflammation